Self-Actualization, Individuation and Self-Realization to Search the True Self: A Comparative Study of Siddhartha and a Portrait of the Artist as a Young Man - Aslam, Ferva; Akhter, Saira; Aslam, Nimra (Pakistan Journal of Humanities and Social Sciences, 2023)
This paper stresses the need for self-actualization through the comparative analysis of Herman Hesse (1951)and James Joyce’s A Portrait of the Artist as a Young Man (D. M. I. H. JAMES, 2009) by instilling the critical lenses of self-actualization, individuation, and self-realization espoused by Abraham Maslow and Carl Jung. It attempts to investigate the quest for the true self of Siddhartha and Stephen Dedalus in different circumstances and scenarios. Both of them are motivated to know their actual self as their all needs are already satisfied according to Maslow’s hierarchy of needs. Maslow and Jung have theorized the need to explore the actuality of self and the process of individuation respectively to achieve psychological development. Jungian archetypes and Maslow’s hierarchy of needs lead toward the final product which is a realized self. This process of discovering the self can never be a linear phenomenon. Siddhartha’s search for Atman and Stephen Dedalus’ search for artistic grandeur paved the way to get their true identity. This self-centered development ensures self-actualization which is a lifelong process with no final destination.